O Sistema Único de Saúde e seus alcances : reflexões acerca do processo de trabalho do consultório na rua - Duarte, Afrannia Hemanuelly Castanho (2018)
The present dissertation systematizes the path and the results of the research developed during the Master's in Social Work in the Graduate Program of the School of Humanities of PUCRS. The main purpose was to analyze the work process and the conceptions of reception in health in the street space to identify the perception of the professionals of the Street Clinic and the users of the National Movement of Street Population (MNPR) in Porto Alegre to offer subsidies for the effective reception of this population and their rights guarantee. We start from the understanding of the critical dialectical method and we used the mixed approach to analyze quantitative and qualitative data. We used the technique of bibliographical and empirical research from the semi structured interviews conducted with the subjects. Our research was made of twelve (12) workers at the Street Clinic, which corresponds to a public service, managed by the Porto Alegre City Hall and the fifteen (15) representatives of the MNPR of the same municipality. The subjects of the study were defined by sample of the intentional type and the data collected through interviews with six (6) workers and four (4) members (representative) of the MNPR. It is possible to affirm that the conception of health reception in the street space for workers is intertwined with work process’ strategies, based on SUS that guarantee the access of this population to health and intersectoral services. These strategies are entangled with active pursuit, approach, listening, welcoming, bonding, trust, sensitivity, persistence, and others. About the users, conception doesn’t pervade both the applicability and construction of this work process as for the workers, but it happens through the perception and sense of who receives this reception, and how this team reaches them all. The users show us perceptions and meanings of being treated as human rights by this team, who respect their ways of life and build relationships of affection and equality.